Regulation of the AcrAB-TolC efflux pump in Enterobacteriaceae - Weston, Natasha; Sharma, Prateek; Ricci, Vito; Piddock, Laura J.V. (Research in microbiology, 2018)
Bacterial multidrug efflux systems are a major mechanism of antimicrobial resistance and are fundamental to the physiology of Gram-negative bacteria. The resistance-nodulation-division (RND) family of efflux pumps is the most clinically significant, as it is associated with multidrug resistance. Expression of efflux systems is subject to multiple levels of regulation, involving local and global transcriptional regulation as well as post-transcriptional and post-translational regulation. The best-characterised RND system is AcrAB-TolC, which is present in Enterobacteriaceae. This review describes the current knowledge and new data about the regulation of the acrAB and tolC genes in Escherichia coli and Salmonella enterica.